Multiple CH/π Interactions Maintain the Binding of Aflatoxin B1 in the Active Cavity of Human Cytochrome P450 1A2 - Jun Wu; Sisi Zhu; Yunbo Wu; Tianqing Jiang; Lingling Wang; Jun Jiang; Jikai Wen; Yiqun Deng (Toxins, 2019)
Human cytochrome P450 1A2 (CYP1A2) is one of the key CYPs that activate aflatoxin B1 (AFB1), a notorious mycotoxin, into carcinogenic exo-8,9-epoxides (AFBO) in the liver. Although the structure of CYP1A2 is available, the mechanism of CYP1A2-specific binding to AFB1 has not been fully clarified. In this study, we used calculation biology to predict a model of CYP1A2 with AFB1, where Thr-124, Phe-125, Phe-226, and Phe-260 possibly participate in the specific binding. Site-directed mutagenesis was performed to construct mutants T124A, F125A, F226A, and F260A. Escherichia coli-expressed recombinant proteins T124A, F226A, and F260A had active structures, while F125A did not. This was evidenced by Fe2+∙Carbon monoxide (CO)-reduced difference spectra and circular dichroism spectroscopy. Mutant F125A was expressed in HEK293T cells. Steady kinetic assays showed that T124A had enhanced activity towards AFB1, while F125A, F226A, and F260A were significantly reduced in their ability to activate AFB1, implying that hydrogen bonds between Thr-124 and AFB1 were not important for substrate-specific binding, whereas Phe-125, Phe-226, and Phe-260 were essential for the process. The computation simulation and experimental results showed that the three key CH/π interactions between Phe-125, Phe-226, or Phe-260 and AFB1 collectively maintained the stable binding of AFB1 in the active cavity of CYP1A2.